Predicting the true extent of glioblastoma based on probabilistic tractography - Kis, David; Szivos, Laszlo; Rekecki, Mark; Shukir, Bayan Salam; Mate, Adrienn; Hideghety, Katalin; Barzo, Pal (Frontiers in Neuroscience, 2022)
Glioblastoma is the most frequent type of primary brain tumors. Despite the advanced therapy, most of the patients die within two years after the diagnosis. The tumor has a typical appearance on MRI: a central hypointensity surrounded by an inhomogeneous, ring-shaped contrast enhancement along its border. Too small to be recognized by MRI, detached individual tumor cells migrate along white matter fiber tracts several centimeters away from the edge of the tumor. Usually these cells are the source of tumor recurrence. In case the infiltrated brain areas could be identified, longer survival time could be achieved through supratotal resection and individually planned radiation therapy. Probabilistic tractography is an advanced imaging method that can potentially be used to identify infiltrated pathways, thus the real extent of the glioblastoma. In our study we enrolled twenty high grade glioma patients. Probabilistic tractography was started from the tumor. The location of tumor recurrence on follow up MRI was considered as the primarily infiltrated white matter tracts. The results of probabilistic tractography were evaluated at thirteen different thresholds and the overlap with the tumor recurrence of each threshold level was defined to calculate the sensitivity and specificity. On the group level sensitivity (81%) and specificity (90%) were the most reliable at 5% threshold level. There were two outliers in the study group with high specificity but very low sensitivity. According to our results, probabilistic tractography can help to define the true extent of the glioblastoma at the time of diagnosis with high sensitivity and specificity. Individually planned surgery and irradiation could provide a better survival chance to these patients.